A Joint Evaluation of Neurohormone Vasopressin-Neurophysin II-Copeptin and Aortic Arch Calcification on Mortality Risks in Hemodialysis Patients - Chang, Jia-Feng; Chou, Yu-Shao; Wu, Chang-Chin; Chen, Po-Cheng; Ko, Wen-Chin; Liou, Jian-Chiun; Hsieh, Chih-Yu; Lin, Wei-Ning; Wen, Li-Li; Chang, Shu-Wei; Tung, Tao-Hsin; Wang, Ting-Ming (Frontiers in Medicine, 2020)
Objective: Systemic hypoperfusion is intricately involved in neurohormone secretion, vascular calcification (VC) related impaired vasodilation and luminal stenosis. We aim to investigate neurohormonal effects of vasopressin-neurophysin II-copeptin peptide (VP) on all-cause and cardiovascular (CV) mortality in maintenance hemodialysis (MHD) patients with advanced aortic arch calcification (AAC). Methods: Unadjusted and adjusted hazard ratios (aHRs) of mortality risks were analyzed in different groups of VP and AAC. The modification effect between higher VP and advanced AAC on mortality risk was examined using an interaction product term. Results: In multivariate analysis, higher VP predicted all-cause and CV mortality (aHR: 2.2 (95% confidence interval (CI): 1.1–4.5)) and 2.6 (95% CI: 1.1–4.6), respectively). Advanced AAC was associated with incremental risks of all-cause and CV mortality (aHR: 2.1 (95% CI: 1.1–4.0）and 2.5 (95% CI: 1.0–4.3), respectively). Patients with combined higher VP (> 101.5 ng/mL) and advanced AAC were at the greatest risk of all-cause and CV mortality (aHR: 4.7 (95% CI: 1.2–16.2）and 4.9 (95% CI: 1.1–18.9), respectively). Interactions between VP and AAC with respect to all-cause and CV mortality were statistically significant. Conclusion：Combined VP and AAC predict not only all-cause but also CV death in MHD patients, and a joint evaluation is more comprehensive than single marker. In light of neurohormonal effects on vital organ perfusion and ischemic events, VP and AAC could act as more robust dual marker for prognostic assessment.